Chemistry and Biochemistry of Food - Pérez-Castiñeira, Jose (De Gruyter Textbook, 2024)
This book provides an excellent platform for understanding the chemical processes involved in food transformation. Starting with the examination of major food components, such as water, carbohydrates, lipids, proteins and minerals, the author further introduces the biochemistry of digestion and energy metabolism of food ingredients. The last section of the book is devoted to modern food technologies and their future perspectives.